The structure and meaning of Bādarāyaṇa's Brahma sūtras: a translation and analysis of adhyaya 1 - Adams, George C. (Motilal Banarsidass Publishers, 1993)
Interpretation of the Brahmasūtra of Bādarāyaṇa, work on Vedanta philosophy